PP09 Cultural barriers to healthy eating in Saudi adults with and without type 2 diabetes (T2D). (2nd September 2014) - Al-Khudairy, L; Stranges, S; Al-Dagheri, N; Al-Attas, O; Alokail, M; Al-Kharfy, K; Kumar, S; Rees, K
Abstract : Background: Strong Islamic beliefs and food hospitality are features of the Saudi culture where the prevalence of T2D is high at 30%. Extremely few studies have assessed barriers to healthy eating within this context. The aim of this study was to use qualitative and quantitative methods to identify barriers to healthy eating among Saudi adults with and without T2D. Methods: Structured face-to-face interviews were conducted at six primary health care centres in Saudi. The sample was a convenience subsample of 108 from the Riyadh Cohort-2 study of Saudi adults from both genders with or without T2D. T2D was previously diagnosed by the physician. The questionnaire used included three sections, one included open-ended questions to elicit free text responses, designed and piloted for this study. The remaining sections included close-ended questions from two pre-developed and pre-tested questionnaires from Saudi. Free text data were analysed thematically using some principles of the grounded theory including the constant comparison method. The one sheet of paper method was used to elicit themes. Quantitative data from the two questionnaires were reported as frequencies (%) with gender and diabetes stratification. Results: A total of 108 participants were interviewed, 23.1% females and 76.9% males, mean age 43 years, 38.9% with T2D. Within the whole sample two main themes were identified: lack of knowledge and Saudi cultural issues. Lack of knowledge included unawareness of health education services, dietary misconceptions and food confusion. From the quantitative data it was found that lack of knowledge was higher among diabetics (16.7%) in comparison to non-diabetics (3.6%). Dietary misconceptions included: snacking is essential for people with T2D (83.3%) and bitter food will normalise hyperglycemia (66%). Food confusion was apparent among participants, e.g. cheese and olive oil are carbohydrates. Cultural issues included reliance, lack of willpower and lack of social support. Participants relied on others (God/health professionals) to take care of their health and lifestyle. Insistence to overeat during social occasions and lack of family support prevented participants from engaging in healthy eating. From the quantitative data lack of willpower was reported by 48% of participants and there was no difference across groups, resistance to change was stronger among females. Conclusion: Lack of knowledge and cultural issues are barriers to healthy eating in Saudi amongst those with and without T2D which would impact on the countries high prevalence of T2D. Further studies are required to inform culturally tailored dietary awareness campaigns.